Team Work Practices and Employee Performance in Local Government Authorities in Tanzania - Mnasi, Haji M; Matoka, Chacha; Raphael, Gwahula (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This paper examined the effects of team work practices on employee performance of local government authorities in Tanzania. The specific objectives were to; determine the influence of shared vision, employee respect, employee ethics, collective decision, team level trust, intrapersonal skills and team cohesiveness on employee performance in LGAs. The study used multiple regression analysis to test the set hypotheses and construct the model. The study was based on cross-sectional survey design in which the quantitative approach was used to collect and analyse data from 368 employees. Research data was collected using a structured survey questionnaire as a research instrument where both descriptive and inferential statistics were used to arrive at conclusions. The study findings showed that shared vision, intrapersonal skills, trust and cohesiveness had the statistically positive and significant relationship between teamwork practice and employee performance. Further, findings revealed that shared decision, respect and workplace ethics were statistically insignificant. The study concluded that LGAs should create an environment that assists shared decision, respect and workplace ethics since this in turn will increase performance of employees. The study recommends team work practices be considered as part of organisations strategy to improve employee performance.